Rekonstruksi Pendidikan Agama Islam Inklusif dalam Membangun Kesadaran Pluralisme Agama - Siswanto Siswanto (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2017)
In an artificial and simplified view, religious plurality is seen as a trigger for violence and religious conflict. Religious education has also been accused of failing to diversify. Religious education should be used as a vehicle to develop universal morality while fostering an inclusive attitude, instead tends to present exclusive and dogmatic face. Therefore, this attitude of exclusiveness needs to be constructed in the inculcation of inclusive values in cultural, religious, racial and other backgrounds, namely education that receive and accommodative to all religious pluralism. Religious education needs to emphasize how to teach about religion that involves a historical and a comparative approach. It is useful to raise the learners’ awareness about the universal and particular aspects of religious teachings.